Is Diclofenac Gargle Effective in Alleviating Post-Tonsillectomy Pain in Adults? - Acharya, Anup; Singh, Madan Mohan; Panday, Bhuwan Raj; Pokharel, Bandana; Pandit, Shiva Bhushan; Bartaula, Suman (Birat Journal of Health Sciences, 2020)
Introduction: Pain in the post-operative period is a major concern following tonsillectomy in an adult resulting in prolonged hospital stay, decreased oral intake and absence from work. Various techniques and medications have been tried to reduce the pain. Objectives We attempted to study the efficacy of diclofenac gargle in reducing the post-tonsillectomy pain in adults. Methodology We conducted a double-blind randomized study in patients 18 years or older undergoing tonsillectomy. Cases were given diclofenac gargle in post-operative period whereas controls were given normal saline gargle. Other modality of treatment and medication were same in both the groups. Pain was assessed at rest and during swallowing with Visual Analogue Score (VAS) on first and second post-operative day, and then at the end of first and second week of the surgery. Pain scores between two groups were compared. Results There were 64 participants equally divided into cases and controls by block randomization. Pain score during swallowing was significantly less in cases. The difference at rest was not significant at any point of time studied. The pain gradually increased over a week in both the groups and then rapidly decreased by the end of second week. Conclusion Diclofenac gargle is effective in reducing the posttonsillectomy pain, especially during swallowing, in adults.